Reflection of Pancasila Value in Tulungagung Tiban Dance Harmony: Tradition and Unity in Cultural Arts - Rima Amalia Rahman (Unika Santu Paulus Ruteng, 2024)
Indonesia is a country rich in ethnic, racial, religious, ethnic and cultural diversity. Of the various cultures that spread from sabang to merauke, there is one of the Tiban Dance cultures originating from Wajak Village, Boyolangu District, Tulungagung Regency, East Java. Tiban dance is a ritual or tradition to ask God for rain that is performed during the dry season. Tiban dance comes from the word